Earthquakes and Landslides Preparedness Planning in Kenya (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Kenya faces significant seismic and landslide risks due to its location along the East African Rift System. Historical earthquakes, such as the 1928 Subukia event (magnitude 6.9), have caused widespread damage, and recent deadly landslides, including the 2019 West Pokot disaster, have resulted in over 70 fatalities and the displacement of thousands. The study employs a comprehensive analytical framework encompassing vulnerability assessment, risk assessment, preparedness measures, mitigation strategies, response mechanisms, and rehabilitation protocols. A vulnerability matrix identifies residential buildings, informal settlements, rural hill communities, and vulnerable populations (children, elderly, persons with disabilities) as high-risk elements, while a risk assessment matrix reveals that landslides present more frequent and immediate threats compared to earthquakes, which though less frequent, carry potential for devastating impacts. The findings indicate that effective preparedness requires integrating early warning systems, public education, emergency drills, stockpiling of relief supplies, and evacuation planning. Mitigation strategies include hazard mapping, enforcement of building codes, slope stabilization, reforestation, and land-use planning regulations. The study highlights the stark implementation divide between developed nations with institutionalized preparedness and developing countries like Kenya facing challenges of limited resources, weak enforcement, fragmented coordination, and systemic vulnerabilities. The paper concludes that multi-faceted, collaborative, and continuous preparedness planning, incorporating scientific data with community-based approaches, is essential for reducing disaster impacts, saving lives, and minimizing economic losses. Recommendations include strengthening institutional capacity, enforcing building regulations, investing in early warning technologies, promoting community awareness, and mainstreaming disaster risk reduction into national and county development plans.